Therapeutic efficacy of artemether–lumefantrine in North-Eastern states of India and prevalence of drug resistance-associated molecular markers - Shreelekha Dutta; Sri Krishna; Anup Kumar Vishwakarma; Sweta Mishra; Sushrikanta Khandai; Disphikha Goswami; Soni Kumari; Nazia Ali; Anil Kumar Verma; Kuldeep Singh; Aparup Das; Anup R. Anvikar; et al. (Malaria Journal)
Abstract Background Plasmodium falciparum is the main cause of malaria in North-Eastern (NE) states of India. Artemether–lumefantrine (AL) was introduced as first-line therapy against uncomplicated P. falciparum cases in 2013 after the emergence of resistance to sulfadoxine–pyrimethamine. The aim of the study was to assess the therapeutic efficacy of AL and status of molecular markers in the circulating parasites. Methods Therapeutic efficacy of AL was assessed in NE states as per World Health Organization guidelines. Patients with P. falciparum positive peripheral blood smear were enrolled and treated with AL and clinical and parasitological parameters were monitored over a 28-day follow-up period. Furthermore, the pfmdr1, pfdhfr, pfdhps and pfk13 genes were amplified and sequenced for mutation analysis. Results A total of 231 cases were enrolled and therapeutic efficacy was determined in 215 (93.1%) patients who completed their 28 days’ follow-up while 10 patients withdrew and 6 were lost to follow up during study. Overall 99.5% and 98.6% of adequate clinical and parasitological response was observed with and without PCR correction, respectively. Only three cases (1.4%) of late parasitological failure were observed in Mizoram site. One case of recrudescence and two cases of reinfection were detected by msp1 and msp2 genotyping. Mutation analysis showed the 15.8%, 100%, 90.5% mutants in pfmdr1, pfdhfr and pfdhps gene respectively and three non-synonymous mutations were also found in pfk13gene. Conclusions This study reports that AL is efficacious against uncomplicated P. falciparum cases in NE states of India. However, prevalence of mutations in molecular marker associated with anti-malarial resistance (pfmdr1, pfdhfr, pfdhps and pfk13) gene indicate possible emergence of drug resistance. This is to underline the fact that the drug is efficacious for now, but rising mutations indicate that continuous monitoring is essential for effective treatment regime.